The method and apparatus for degumming of crude palm oil by membrane filtration. - Baharin, Badlishah Sham (2008)

(untitled)
The present invention provides a process for the degumming of crude palm oil by way of membrane filtration. The process involves melting of crude palm oil to provide a homogenized oil, feeding of the homogenized oil into a microfiltration apparatus whereby the oil is passed trough a membrane filter (19) contained therein and recovering the permeate flux that pass through the membrane filter (19). The membrane filter (19) has a pore size selected to be small enough to remove substantially all phospholipids and the process further includes recycling of the permeate and retentate into the microfiltration apparatus. The present invention also provides a microfiltration apparatus that consists of a feed tank (10) containing the crude palm oil, a feed pump (12) that pumps the crude palm oil into a heat exchanger (14) for controlling the liquid temperature, a filtration module (19) for the filtration of the crude pal oil at a particular temperature and pressure, and valves (13, 22) for controlling the flow of feed and retentate. In a preferred embodiment, the apparatus uses polyethersulfone membrane of a pore size sufficient to remove phospholipids and other impurities.